Expanding the HPSE2 Genotypic Spectrum in Urofacial Syndrome, A Disease Featuring a Peripheral Neuropathy of the Urinary Bladder - Beaman, Glenda M.; Lopes, Filipa M.; Hofmann, Aybike; Roesch, Wolfgang; Promm, Martin; Bijlsma, Emilia K.; Patel, Chirag; Akinci, Aykut; Burgu, Berk; Knijnenburg, Jeroen; Ho, Gladys; Aufschlaeger, Christina; et al. (Frontiers in Genetics, 2022)
Urofacial (also called Ochoa) syndrome (UFS) is an autosomal recessive congenital disorder of the urinary bladder featuring voiding dysfunction and a grimace upon smiling. Biallelic variants in HPSE2, coding for the secreted protein heparanase-2, are described in around half of families genetically studied. Hpse2 mutant mice have aberrant bladder nerves. We sought to expand the genotypic spectrum of UFS and make insights into its pathobiology. Sanger sequencing, next gen-eration sequencing and microarray analysis were performed in four previously unreported families with urinary tract disease and grimacing. In one, the proband had kidney failure and was homozy-gous for the previously described pathogenic variant c.429T>A, p.Tyr143*. Three other families each carried a different novel HPSE2 variant. One had homozygous triplication of exons 8 and 9; another had homozygous deletion of exon 4; and another carried a novel c.419C>G variant encod-ing the missense p.(Pro140Arg) in trans with c.1099-1G>A, a previously reported pathogenic splice variant. Expressing the missense heparanase-2 variant in vitro showed that it was secreted as normal, suggesting that 140Arg has aberrant functionality after secretion. Bladder autonomic neurons emanate from pelvic ganglia where resident neural cell bodies derive from migrating neu-ral crest cells. We demonstrated that, in normal human embryos, neuronal precursors near the de-veloping hindgut and lower urinary tract were positive for both heparanase-2 and leucine rich re-peats and immunoglobulin like domains 2 (LRIG2). Indeed, biallelic variants of LRIG2 have been implicated in rare UFS families. The study expands the genotypic spectrum in HPSE2 in UFS and supports a developmental neuronal pathobiology.